The Effect Of Diesel And Bio-Diesel Fuel Deposit Layers On Heat Transfer - Yusmady, Mohamed Arifin; Shamsudin, Shamsul Anuar; Mokhtar, Muhammad Zhafri; Syahrial, Fadhli; Akop, Mohd Zaid; Herawan, Safarudin Gazali (Penerbit UTeM, 2019)
The adhesion of deposits on the combustion chamber wall surface affecting the heat transfer process in an engine that cause engine knock, increase NOx and increase soot generation during the combustion process. The effect will be more significant when utilizing bio-diesel fuel due to its higher density and viscosity. Thus, this study is intended to investigate the effect of diesel and bio-diesel fuels deposit layers on heat transfer. In this study, deposit layer of diesel fuel (DF) and 5% palm oil based bio-diesel fuel blends (B5) were prepared for surface temperature at 250°C and 357°C by using a hollow cylinder heater. Then, the hollow cylinder covered with deposit layer in its inner surface was inserted in a heat transfer chamber apparatus to investigate its effect on heat transfer to surrounding. Deposit layer for DF that was prepared at surface temperature of 357°C was able to act as insulator which prevents the heat from transferring to the surrounding compared to deposit layer formed at lower surface temperature. However, deposit layer of B5 prepared at surface temperature of 250°C have better insulator properties compared to DF at the same surface temperature.